EXISTENCE AND RESISTANCE OF WOMEN IN THE NOVEL KEBERANGKATAN BY NH DINI AND ITS IMPLICATIONS FOR NOVEL READING SKILLS - Saprilia, Dian Fadila; Purbarani, Etsa; Parai, Hestiyani (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to explore the theme of women’s existence and resistance in Keberangkatan, a novel by Nh. Dini, using Simone de Beauvoir’s existentialist feminism and James C. Scott’s theory of resistance. The main character, Elisa, is potrayed as a woman who rejects subordinate roles and seeks authentic existance through work, education, financial independence, and personal freedom. Her resistance, both overt and covert, is examined through Scott’s concepts of public and hidden transcripts. This research uses a qualitative-descriptive method with literary analysis techniques. The results show that Elisa’s journey reflects not only individual resistance to patriarchal norms but also a broader social transformation. In line with the Merdeka Curriculum, which emphasizes literacy and critical thinking, the novel can serve as learning material in literature instruction. Students can be encouraged to relate fictional texts to social realities, build gender awareness, and critically reflect on personal and societal roles.